Context-based learning in higher education 1992-2023: trends and outstanding research areas from Scopus database - Toan, Hua Thi; Hang, Nguyen Thi Thu; Hai, Trinh Thanh; Ngu, Pham Nguyen Hong; Thao, Trinh Thi Phuong (Institute of Advanced Engineering and Science, 2025)
Context-based learning (CBL) has recently gained increasing attention as a pedagogical approach in higher education to enhance students’ understanding and problem-solving skills in real-world scenarios. This study aims to provide an overview of CBL-related issues in higher education as documented in publications from the Scopus database. A bibliometric analysis was employed to review 153 publications. The results show that articles on this topic have become more prevalent from 2009 to 2023, particularly in 2020 and 2022. A total of 443 authors from 160 institutions across 52 countries have contributed to research on this subject, with the USA being the most engaged nation in CBL studies in higher education, having the highest number of publications, citations, and research funding. The journal with the most publications on this topic is the International Journal of Science Education, classified in the Q1 category. Key research trends have been identified, focusing on applying CBL in engineering, software technology, teacher training, and nursing programs and its implementation in collaborative learning environments, distance learning, and online education. The findings are a critical resource for scholars interested in advancing research on CBL in higher education.